2007
DOI: 10.1590/s0104-530x2007000200010
|View full text |Cite
|
Sign up to set email alerts
|

Metodologia de Shigeo Shingo (SMED): análise crítica e estudo de caso

Abstract: Resumo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 9 publications
0
5
0
12
Order By: Relevance
“…Nessa etapa envolve em examinar os dados de operação de setup interno e externo, identificar possíveis ações de melhoria com objetivo de atingir tempo de setup menor que dez minutos. Sugai, Mcintosh, Novaski (2007) afirmam que importantes opções de melhorias podem surgir no Estágio 3 e podem ser mais relevantes na redução do tempo de setup. Os métodos apresentados reduzem os setups até 5% dos seus tempos anteriores, onde trocas podem ser concluídas em alguns segundos com a eliminação dos ajustes e a utilização do sistema do mínimo múltiplo comum.…”
Section: Troca Rápida De Ferramentasunclassified
See 2 more Smart Citations
“…Nessa etapa envolve em examinar os dados de operação de setup interno e externo, identificar possíveis ações de melhoria com objetivo de atingir tempo de setup menor que dez minutos. Sugai, Mcintosh, Novaski (2007) afirmam que importantes opções de melhorias podem surgir no Estágio 3 e podem ser mais relevantes na redução do tempo de setup. Os métodos apresentados reduzem os setups até 5% dos seus tempos anteriores, onde trocas podem ser concluídas em alguns segundos com a eliminação dos ajustes e a utilização do sistema do mínimo múltiplo comum.…”
Section: Troca Rápida De Ferramentasunclassified
“…Síntese Conclusões Sugai et al (2007) Analisa as lacunas da metodologia SMED e discute alguns pontos que interfere no tempo de setup: interferência da sequência de lote, necessidade de ajustes no projeto das máquinas e perdas de produção na recuperação da capacidade produtiva no período que antecede o setup e pós setup. Constatou que a adoção da técnica SMED, com um curto changeover, possibilita um processo produtivo mais estável, aumento de produtividade e redução de custos, além de oferecer um grande mix de produtos, com a redução dos tamanhos dos lotes de produção e maior agilidade para responder às variações da demanda, com a redução dos lead times.…”
Section: Autoresunclassified
See 1 more Smart Citation
“…Neumann and Ribeiro (2004) analyzed how a supplier development program achieved a 50 % of improvement in the set up time of the firm. Sugai, McIntosh and Novaski (2007), addressing a single case study, concluded that the sequencing of production lots, the acceleration (during the setup) and deceleration (during post-setup) periods and the need to maintain rigorous set up times achieved are very important topics. Clearly, studies concerning SMED implementation and innovation process are in short supply.…”
Section: Single-minute Exchange Of Diementioning
confidence: 99%
“…In order to implement this process-based innovation, setup operations have to be standardized and properly documented in order to ensure that production workers follow all of the parameters of that process (Nicholas, 1998). Although some SMED results have been described and presented widely (Monden, 1984;Johansen and McGuire, 1986;Sepheri, 1987;Quinlan, 1987;Noaker, 1991;Gilmore and Smith, 1996;McIntosh et al, 2000), studies about SMED implementation are in short supply in Ibero-America (Silva and Duran, 1998;Fogliatto and Fagundes, 2003;Satolo and Calarge, 2008;Sugai, McIntosh and Novaski, 2007). As a consequence, and taking into account a SMED pilot project implemented in a manufacturing firm in the North of Portugal during 2008, the major endeavor of this paper is to present a case study about the implementation of the SMED methodology and report the insights gained.…”
Section: Introductionmentioning
confidence: 99%